A Companion to the British and Irish Short Story - Malcolm, David; Malcolm, Cheryl Alexander (Blackwell companions to literature and culture, 2008)
A Companion to the British and Irish Short Storyprovides a comprehensive treatment of short fiction writing and chronicles its development in Britain and Ireland from 1880 to the present.Provides a comprehensive treatment of the short story in Britain and Ireland as it developed over the period 1880 to the presentIncludes essays on topics and genres, as well as on individual texts and authorsComprises chapters on women’s writing, Irish fiction, gay and lesbian writing, and short fiction by immigrants to Britain